Photoacoustic Spectroscopy in the Optical Characterization of Foodstuff: A Review - Claudia Hernández-Aguilar; Arturo Domínguez-Pacheco; Alfredo Cruz-Orea; Rumen Ivanov (Journal of Spectroscopy)
In this review, the application of the photoacustic spectroscopy (PAS) is presented as an option to evaluate the quality of food. This technique is a type of spectroscopy based on photothermal phenomena, which allow spectroscopic studies. According to the literature review, it was found that its application is increasing in several countries. Spectroscopic studies carried out by employing PAS in the food industry include, among others, fruit, vegetables, condiments, grains, legumes, flours, “tortillas,” milk, water, eggs, etc. Additionally, this technique has been used to evaluate adulterated, irradiated, and contaminated food and so on. The literature review has shown the applicability of PAS to one of the problems of the real world, i.e., food quality assessment. Therefore, PAS can contribute in the future with a wide potential for new applications in the food agroindustry.